Serum Mac-2 binding protein glycosylation isomer and galectin-3 levels in adult-onset Still’s disease and their association with cytokines - Yoshida, Shuhei; Koga, Tomohiro; Fujita, Yuya; Yatsuhashi, Hiroshi; Matsumoto, Haruki; Sumichika, Yuya; Saito, Kenji; Sato, Shuzo; Asano, Tomoyuki; Kobayakawa, Masao; Ohira, Hiromasa; Mizokami, Masashi; et al. (Frontiers in Immunology, 2024)
Background: Autoinflammation with cytokine dysregulation may be implicated in the pathophysiology of adult-onset Still's disease (AOSD); however, the relationship between galectins and cytokines in patients with active AOSD remains unknown. We aimed to examine the relationship between circulating cytokines/chemokines and galectin-3 (Gal-3) or its ligand, Mac-2 binding protein glycosylation isomer (M2BPGi), in Japanese patients with AOSD.Methods: We recruited 44 consecutive patients diagnosed with AOSD according to the Yamaguchi criteria, 50 patients with rheumatoid arthritis (RA) as disease controls, and 27 healthy participants. Serum M2BPGi levels were directly measured using a HISCL M2BPGi reagent kit and an automatic immunoanalyzer (HISCL-5000). Serum Gal-3 concentrations were measured by enzyme-linked immunosorbent assay. The serum levels of 69 cytokines were analyzed in patients with AOSD using a multi-suspension cytokine array. We performed a cluster analysis of each cytokine expressed in patients with AOSD to identify specific molecular networks.Results: Significant increases in the serum concentrations of Gal-3 and M2BPGi were found in the serum of patients with AOSD compared with patients with RA and healthy participants (both p <0.001). There were significant positive correlations between serum Gal-3 levels and AOSD disease activity score (Pouchot score, r=0.66, p <0.001) and serum ferritin levels. However, no significant correlations were observed between serum M2BPGi levels and AOSD disease activity scores (Pouchot score, r = 0.32, p = 0.06) or serum ferritin levels. Furthermore, significant correlations were observed between the serum levels of Gal-3 and various inflammatory cytokines, including interleukin-18, in patients with AOSD. Immunosuppressive treatment in patients with AOSD significantly reduced serum Gal-3 and M2BPGi levels (p = 0.03 and 0.004, respectively).Conclusions: Although both Gal-3 and M2BPGi were elevated in patients with AOSD, only Gal-3 was a useful biomarker for predicting disease activity in AOSD. Our findings suggest that circulating Gal-3 reflects the inflammatory component of AOSD, which corresponds to proinflammatory cytokine induction through inflammasome activation cascades.